Analisis Input Output 2016 Nasional; Dampak Ekonomi Atas Pembangunan Infrastruktur di Indonesia - Purnomo, Budi (Melati Institute, 2024)
Infrastructure development is an activity that includes construction work to build or improve infrastructure capabilities, and/or infrastructure management activities and/or infrastructure maintenance. According to the indicative ceiling in the 2025 Draft State Budget (binakonstruksi.pu.go.id, 2024) of 75.63 trillion consisting of water resources sector of 26.53 trillion, bina marga sector of 32.31 trillion, cipta karya sector of 10.48 trillion and housing sector of 4.53 trillion. The infrastructure budget allocation approach is expected to realize regional development targets, create economic growth and be able to overcome a number of welfare problems faced by the community such as poverty, unemployment and income inequality, in order to realize the vision of a golden Indonesia in 2045. Therefore, in this study, the author wants to know the extent of the economic impact of the infrastructure budget allocation, especially at the PUPR ministry according to the indicative ceiling of the Draft State Budget 2025 with the 2016 Indonesian input output model (52 sectors) in the construction sector, water supply, waste management, waste, and recycling, land transportation and whether the budget allocation will have an economic impact as expected,The national economic impact of the infrastructure budget allocation plan at the Ministry of PUPR listed in the indicative ceiling of the 2025 Draft State Budget using the 2016 Indonesian input output analysis model provides a multiplier impact and economic impact in terms of increased economic output, labor income and employment in all sectors of the economy. The largest sectors that have an impact on employment and increased community income are the sectors of water supply, waste management, waste and recycling, land transportation and construction.